Ocena razpoložljive vetrne energije - Zajec, Boštjan (Matrika, 2016)
In recent times, the demand of alternative energy is increasing and as a renewable resource, wind power is gaining its popularity. While many countries have had great success with its implementation, there are still many misconceptions about its realistic potentials and physical bacground. In the article we discuss the bascis of wind physics (aerodynamics) and wind site evaluation on the example of Kredarica micro wind turbine.
Keywords: aerodinamika; aerodynamics; izkoristek; obnovljivi viri energije; renewable energy resources; veter; vetrna energija; vetrnice; wind power; wind site evaluation